Correlation Profile of Cognition Levels and Student Ability to Solve Problems in Biodiesel Synthesis - Hulyadi Hulyadi; Faizul Bayani; Muhali Muhali; Yusran Khery; Gargazi Gargazi (Jurnal Penelitian Pendidikan IPA, 2023)
Covid-19 has had a huge impact in all sectors. The socio-economic sector experienced the heaviest impact. One of the sectors affected is the world of education. Education is now transforming from face-to-face learning to online learning. Online learning is very helpful for students during covid-19. In addition to having a positive value, online learning also contains a negative value. For example, students' interest in reading increases, but on the other hand, students' reading power is low. Low reading power has an impact on decreasing the cognitive level of students. The purpose of this research is to first identify the cognitive level profiles and students' abilities in solving problems in the synthesis of biodiesel from used cooking oil. Analyzing the correlation between cognitive level and students' ability to solve problems. This research is a correlational descriptive research. This research was conducted on fourth semester chemistry education students who were taking an instrument chemistry course and determining the structure of organic compounds. Cognitive level and problem-solving ability were measured using a rubric for assessing cognitive level and student problem-solving ability. The data obtained is then described in graphical form. The data was then tested for correlation using the SPSS product moment correlation test. In this study, it was found that the cognitive level of most students entered at C2 and C3 levels and the average problem solving ability was 53.84. The results of the correlation test show that the cognitive level is positively correlated with the ability of students to solve problems. This is evidenced by the comparison of the value of r count 0.724> r table 0.44. Based on the results of this study, it can be concluded that the cognitive level and problem solving abilities of students are still low. Cognitive level and problem solving ability are positively correlated